The application of "Saddu Aż-Żarī‘ah" in the contemporary Islamic world (The requirement of the wife’s permission when polygamy in the system of the Republic of Indonesia No. 1 of 1974 on marriage, a comparative jurisprudential study) - Al-Farahidy, Khalil; Hamsin, Khaeruddin; Fauzan, Aris (Journal of Islamic Sciences, 2022)
The aim of this research is to know the extent to which the rule of Saddu Aż-Żarīʻah is used in the contemporary Islamic world, especially the country of Indonesia, which has the largest Muslim population. Why Indonesia? Because it is a sign of democracy and does not recognize its Islamism. However, many of its systems were found in compliance with Islamic rules. It's normal; Because with the presence of the majority of Muslims there will be a great effort to make laws that suit the majority. Among the official regulations established by the Indonesian government: Law No. 1 of 1974 on Marriage. One of the points that the researcher is interested in is the ruling on the requirement of permission for the husband when he wants to have polygamy. According to this matter, the researcher tried to explain the exact ruling that this law fits with the rule of blocking the precaution.The researcher followed the original, deductive, comparative, and analytical method. I have come to the conclusion that what is included in this system by requiring the permission of the wife is compatible with the rule of Saddu Aż-Żarīʻah, for the sake of the safety of family life between the spouses in the future. The rule of Saddu Aż-Żarīʻah is one of the principles used by Muslim scholars in the past in establishing rulings, yet it is still used, valid and appropriate with the contemporary Islamic world.
Keywords: polygami; wife's permission; marriage rule; Saddu Aż-Żarī‘ah